Boundaries of Marital and Family Intimacy: From Theory to Empirical Approaches - Piazzesi, Chiara; Blais, Martin; Belleau, Hélène (Enfances, Familles, Générations)

(untitled) (INRS-UCS, 2019)
Research Framework : This article discusses the symbolic, discursive and practical boundaries of intimate relationships. Our approach is inspired by Niklas Luhmann's systems theory. The "boundary" is conceived as an operation of a relationship in relation to itself: the relationship defines itself through its communicative operations and thus defines the legitimate expectations of its members. The relation thus exists as a boundary through its communicative operations, which directly or indirectly determine what it is and what it is not. Symbols, rules of meaning and semantic references are tools used in boundary work. However, the symbols do not define the ways in which these tools may be employed in this work. Objectives : The article has two main objectives. First, by utilizing and defining the concepts of "boundaries" and "boundary work," the paper offers innovative theoretical tools for intimacy research. Second, it demonstrates the empirical utility of these concepts by discussing examples of their application to the study of forms and processes of intimacy in the social sciences. Methodology : Primarily theoretical in focus, the paper begins by conceptually clarifying and defining the concepts of "boundaries" and "boundary work" in the social sciences, and then discusses their applications to intimate, marital and family relationships. Results : The boundaries of relationships emerge from the operationalization of symbols, semantic references or rules of meaning in communication between partners or members of relationships. The symbols used do not determine the methods of their operationalization, which makes it necessary to observe the operations of the boundary work directly in order to describe and understand them. Conclusions : Having explored the theoretical and empirical foundations of the concept of boundaries in the sociology of intimate relations, this paper documents the centrality of semantics and discourse in the boundary work that defines intimate relations. It also shows how the concept captures the operations of self-definition that the relationships themselves need in order to continue to exist.  Contribution:  This article summarizes what is known about the concept of boundaries and shows its heuristic potential for addressing intimate, marital or family relationships. The articles collected in this issue also contribute by demonstrating its relevance in analyzing a diversity of intimate relationships, regardless of their composition, duration, or degrees of stability or institutionalization.